Multimodal nanoparticle‐containing modified suberoylanilide hydroxamic acid polymer conjugates to mitigate immune dysfunction in severe inflammation - Nhu Truong; Andrea L. Cottingham; Shruti Dharmaraj; Jacob R. Shaw; Jackline Joy Martin Lasola; Christopher C. Goodis; Steven Fletcher; Ryan M. Pearson (Wiley, 2024)
Abstract Excessive immune activation and immunosuppression are opposing factors that contribute to the dysregulated innate and adaptive immune responses seen in severe inflammation and sepsis. Here, a novel analog of the histone deacetylase inhibitor (HDACi), suberoylanilide hydroxamic acid (SAHA‐OH), was incorporated into immunomodulatory poly(lactic acid)‐based nanoparticles (iNP‐SAHA) by employing a prodrug approach through the covalent modification of poly(lactic‐co‐glycolic acid) (PLGA) with SAHA‐OH. iNP‐SAHA formulation allowed for controlled incorporation and delivery of SAHA‐OH from iNP‐SAHA and treatment led to multimodal biological responses including significant reductions in proinflammatory cytokine secretions and gene expression, while increasing the survival of primary macrophages under lipopolysaccharide (LPS) challenge. Using a lethal LPS‐induced endotoxemia mouse model of sepsis, iNP‐SAHA administration improved the survival of mice in a dose‐dependent manner and tended to improve survival at the lowest doses compared to iNP control. Further, iNP‐SAHA reduced the levels of plasma proinflammatory cytokines and chemokines associated with sepsis more significantly than iNP and similarly improved inflammation‐induced spleen and liver toxicity as iNP, supporting its potential polypharmacological activity. Collectively, iNP‐SAHA offers a potential drug delivery approach to modulate the multifaceted inflammatory responses observed in diseases such as sepsis.